Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

convert the equation in point-slope form to slope-intercept form:[tex]y - 2 = 3(x - 1)[/tex]

Sagot :

The Slope-Intercept form of the equation of a line is:

[tex]y=mx+b[/tex]

Where "m" is the slope of the line and "b" is the y-intercept.

In this case you have this equation of the line in Point-Slope form:

[tex]y-2=3\mleft(x-1\mright)[/tex]

Then, in order to write it in Slope-Intercept form, you must solve for the variable "y". So you get:

[tex]\begin{gathered} y-2=(3)(x)-(1)(3) \\ y-2=3x-3 \\ y=3x-3+2 \\ y=3x-1 \end{gathered}[/tex]

The answer is:

[tex]y=3x-1[/tex]